Using Thematic Analysis to Understand Teachers Perspectives about Inclusion in Early Childhood Education - Farhan Sarwar, Zikra Faiz, Mohammad Saipol Bin Mohd Sukor (JIE, 2021)
Teachers are an important part of society, and they played a vital role in the development of the country. As inclusive education is becoming a major concern for every country, either they are developed or developing. The study aimed to explore the teacher's perception of Inclusion in Early Childhood Education.